2013
DOI: 10.1098/rsbl.2013.0712
|View full text |Cite
|
Sign up to set email alerts
|

Size and accumulation of fuel reserves at stopover predict nocturnal restlessness in a migratory bird

Abstract: Early arrival at the breeding site positively affects the breeding success of migratory birds. During migration, birds spend most of their time at stopovers. Therefore, determining which factors shape stopover duration is essential to our understanding of avian migration. Because the main purpose of stopover is to accumulate fat as fuel for the next flight bout, fuel reserves at arrival and the accumulation of fuel are both expected to affect stopover departure decisions. Here, we determined whether fuel reser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
23
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 23 publications
(31 reference statements)
7
23
4
Order By: Relevance
“…Migratory restlessness is a key measure in avian migration research, and many studies have used inter-individual variation in migratory restlessness to explain how environmental and intrinsic factors temporally affect migration [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Our findings therefore justify the conclusions of a large body of research on avian migration.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…Migratory restlessness is a key measure in avian migration research, and many studies have used inter-individual variation in migratory restlessness to explain how environmental and intrinsic factors temporally affect migration [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Our findings therefore justify the conclusions of a large body of research on avian migration.…”
Section: Resultssupporting
confidence: 73%
“…As migratory restlessness has also been defined as the activity recorded in a given time period, usually (part of) the night [14,16,[20][21][22]25], we repeated the analyses with migratory restlessness defined as the total number of activity counts recorded between 1 and 5. Levels of migratory restlessness were lower than those observed previously in northern wheatears on Helgoland during spring migration [23]. The most likely explanation for this seasonal difference is that in spring migrants generally travel faster, and make shorter stopovers, than in autumn [31].…”
Section: Resultscontrasting
confidence: 39%
See 1 more Smart Citation
“…That is, which physiological signals tell the brain that the fuel reserves are sufficient to resume migration? This link that connects physiological condition and brain is still unknown.Previous work has shown that fat stores are the best predictor for migratory disposition and stopover duration: Birds with larger subcutaneous (s.c.) fat stores show more migratory restlessness in captivity (8,10,13,14), stay shorter times at stopover sites (9, 11), and migrate faster (12). Because birds fuel their migratory flights primarily through fatty acid metabolism (15-17), we expect that factors reflecting fuel load or the energetic condition must be involved in the behavioral switch between resting at stopover sites and resuming migration.…”
mentioning
confidence: 99%
“…During the migration season energy stores and feeding/refueling rates are a critical determinant modulating migratory behaviour (Fusani et al 2009, Eikenaar and Schläfke 2013, Lupi et al, 2016. In addition, external factors also affect the costs and benefits of migration and can modulate migration behaviours.…”
Section: Introductionmentioning
confidence: 99%